Strategic maneuvering in argumentative parliamentary discourse in the Eastern Cape legislature of South Africa - Mangcunyana, Mteteleli Nelson (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.